2017
DOI: 10.1049/iet-epa.2016.0618
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of motor shape and magnetisation direction to obtain vibration reduction and average torque improvement in IPM BLDC motor

Abstract: An optimal design for the interior permanent magnet (IPM) motor is proposed to reduce vibration and increase average torque, based on simultaneous consideration of the rotor d-axis notch shape, the stator chamfer angle, and the magnetisation direction. The notch shape of the rotor and the chamfer of the stator tooth shape were first reviewed in order to reduce the vibration of the IPM motor; however, the optimal shapes for reduced vibration also reduced the average torque. Then, a design optimisation for avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…After substituting (9) and (13) into (16), it is given that (see (17) and (18)) Equation (17) will be non-zero only when k r = k p ′ ∪ k c ′. Therefore (see (18)) From (18), it is shown that aside from main torque produced by air-gap fundamental flux densities of p p and p c pole pairs, additional ripple torques produced by air-gap space harmonics also exist.…”
Section: Torque Ripple Analysismentioning
confidence: 99%
“…After substituting (9) and (13) into (16), it is given that (see (17) and (18)) Equation (17) will be non-zero only when k r = k p ′ ∪ k c ′. Therefore (see (18)) From (18), it is shown that aside from main torque produced by air-gap fundamental flux densities of p p and p c pole pairs, additional ripple torques produced by air-gap space harmonics also exist.…”
Section: Torque Ripple Analysismentioning
confidence: 99%
“…There are two different approaches to reduce torque ripple in a motor. In the first approach, attempts are made to reduce the torque ripple by modifying the physical structure of the stator and rotor of the motor (including tooth, slots, windings and PMs) [3][4][5][6][11][12][13]. In the second approach, the torque ripple is reduced by applying an appropriate control method, which is the aim of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…Brushless dc motors are popular in a wide range of industrial applications, such as computer peripherals, servo control systems and electrical tools due to their robustness, simplicity, large torque to volume ratio and high-efficiency [1][2][3][4][5][6][7][8][9]. Interior permanent magnet brushless DC (IPMBLDC ) electric motor [10][11][12][13][14][15][16][17] is an important category of these motors, constructed with the permanent magnets inserted into the steel rotor core and does not need to be glued such as in surface mounted permanent magnet motors. The leakage path of interior magnet motors usually includes a saturable magnetic bridge and the web, which will make the coefficient of flux leakage variable.…”
Section: Introductionmentioning
confidence: 99%